A new nanohybrid with BODIPY and Fe3O4 modified graphdiyne oxide in theranostic. (1st October 2022) - Lin, Yanxin; Jiang, Xu; Liu, Yanhui; Wang, Ning; Shi, Ruijie; Wang, Yingpu; Feng, Yaqing; Huang, He; Meng, Shuxian
Abstract: Graphdiyne (GDY) is a new 2D carbon material different from graphene, and its ideal drug carrying and photothermal therapy efficacy had been noticed recently. Graphdiyne-oxide (GDYO), which few phototherapy researches had been reported, has more oxygen functional groups than GDY. Metal-organic framework materials Fe3 O4 @UiO-66-NH2 (FU) can covalently connect to GDYO layers and obtain covalent-organic framework-like structures FUGYO. FU enlarged interlamellar space of GDYO, which avoided the aggregation of FUGYO multiple layers. At the same time, more acetylenic bonds and hydrophilic group were exposed, which brings out advantages like stability, hydrophily, high drug-loading, as well as magnetic targeting and better magnetic resonance imaging efficacy. To promote cancer treatment effect and water solubility, we loaded chemotherapy drug doxorubicin (DOX) in FUGYO, then encapsulated FUGYO/DOX in phosphatidylcholine and fluorescent organic polymer BODIPY-PEG (BP) to integrate image-guided and synergistic therapy in one nanoparticle (BPFG/DOX). Due to the unique structure of BPFG/DOX, the π – π interaction between GDYO and BP improved photodynamic therapy efficiency. About 10 μ g ml −1 BPFG/DOX have nearly 90% cell lethality to MCF-7 (human breast cancer cell line) cells with laser irradiation. In vivo, BPFG/DOX possessed ideal magnetic targeting and effectively inhibited tumor growth in 6 d. In conclusion, BPFG/DOX not only acts as an excellent tumor theranostic agent but also provides a scheme for applying GDYO in the biomedical region.